E-Kuesioner Evaluasi Kualitas Layanan Akademik Universitas Timor Menggunakan Metode Prototype - Eugenius Charles Odja; Darsono Nababan; Yoseph P.K. Kelen (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2024)
In the era of sophisticated technology that brings many changes in various aspects of life, technological developments also have an impact in the field of education. Quality and quality assurance can be seen and measured from the level of student satisfaction during the lecture process and the services provided by academic staff to students. In the implementation of the distribution of academic service evaluation questionnaires at Timor University, they still use paper questionnaires that are distributed to students to be filled in. This results in inefficient time in filling out the questionnaire and requires large costs because it still uses paper media. So a system is needed to handle these problems so that the process of filling out questionnaires can be done centrally in 1 database that has been integrated with a computer system. In some previous studies, the system built in terms of features is quite complete but can only be accessed by 2 users, namely students and the person in charge of the academic section. The account list feature itself by students. So based on the description of the background explanation of the problem in the previous paragraph, a web-based application is needed to handle these problems, namely